Global dimension of the sharing economy - HONCHARENKO Олена (Ius Modernum, 2025)
Global economic challenges, including rising inequality, resource constraints and environmental threats, require the search for new models of economic growth that can ensure sustainable and equitable development. The sharing economy is a progressive alternative to traditional models, focusing on the efficient use of assets through digital platforms, minimising transaction costs and expanding access to basic goods. The phenomenon of the sharing economy as an important driver of global economic transformations is considered, in particular, its impact on increasing resource efficiency, reducing energy intensity and stimulating economic growth. The role of digital platforms in the spread of this model, which provides new mechanisms of value creation, in particular through network effects, is investigated. The methodological basis of the study is a combination of general scientific and special methods, including comparative analysis, generalisation, systematisation, structural approach and content analysis. In practical terms, the study is significant for systematising the models of the sharing economy and analysing their implementation on the example of Airbnb, Uber, and BlaBlaCar. The main drivers (technological innovations, changes in consumer habits, development of digital platforms) and barriers (regulatory restrictions, social and security aspects) of the development of the sharing economy have been identified. The hypothesis has been confirmed that the growing popularity of the sharing economy contributes to an increase in GDP, reducing energy costs and more efficient use of resources. The key social, economic and technological factors that influence its development are identified. The prospects for the integration of the sharing economy into the global economic system, its impact on trade, business models and the labour market are substantiated. The obtained results can be used in the formation of economic policies and strategies for the development of digital platforms, contributing to sustainable economic growth.